Françoise Dolto between relational thinking and Freudian metapsychology - Iwer-Docter, Lukas; Kristensen, Stefan (Psychoanalytic dialogues, 2024)
The aim of this article is to present the work of the French child psychoanalyst Françoise Dolto (1908-1988) and to explore possible contributions to current debates in relational psychoanalysis. We present the historical and conceptual relationship between relational psychoanalysis and French psychoanalysis. Within this context, we will discuss certain key concepts (e.g., unconscious body image, need and desire, symbolic castrations) of Dolto who, in our view, provides an intersubjective understanding of the unconscious that resembles current relational approaches such as Jessica Benjamin’s theory of recognition. We shall discuss Dolto’s embodied understanding of the unconscious and the role of language and intercorporeal resonance and will compare it to Benjamin’s relational approach.
Online veröffentlicht: 22. April 2024
Gesehen am 06.09.2024